2016
DOI: 10.18632/oncotarget.12135
|View full text |Cite
|
Sign up to set email alerts
|

Association between tumor-stroma ratio and prognosis in solid tumor patients: a systematic review and meta-analysis

Abstract: Tumor-related stroma plays an active role in tumor invasion and metastasis. The tumor-stroma ratio (TSR) in the pathologic specimen has drawn increasing attention from the field of predicting tumor prognosis. However, the prognostic value of TSR in solid tumors necessitates further elucidation. We conducted a meta-analysis on 14 studies with 4238 patients through a comprehensive electronic search on databases updated on May 2016 to explore the relationship between TSR and prognosis of solid tumors. The overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
165
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(180 citation statements)
references
References 48 publications
11
165
3
1
Order By: Relevance
“…Recently, a meta‐analysis that reviewed 14 studies on eight different types of malignancies found that TSR was correlated with unfavorable OS ( p < .001, pooled HR = 1.89; 95% CI 1.56–2.29) and disease‐free survival ( p < .001, pooled HR = 2.10; 95% CI 1.67–2.63). Moreover, stroma‐rich cancer was prone to have advanced clinical stage ( p = .012; pooled odds ratio [OR] = 1.68; 95% CI 1.20–2.51) and LN metastasis ( p = .008; pooled OR = 1.72; 95% CI 1.16–2.55) . However, in our study on ICC, TSR was not an independent prognostic factor for survival ( p = .189, HR = 1.399, 95% CI 0.848–2.309 for OS; p = .488, HR = 1.160, 95% CI 0.763–1.763).…”
Section: Discussioncontrasting
confidence: 54%
“…Recently, a meta‐analysis that reviewed 14 studies on eight different types of malignancies found that TSR was correlated with unfavorable OS ( p < .001, pooled HR = 1.89; 95% CI 1.56–2.29) and disease‐free survival ( p < .001, pooled HR = 2.10; 95% CI 1.67–2.63). Moreover, stroma‐rich cancer was prone to have advanced clinical stage ( p = .012; pooled odds ratio [OR] = 1.68; 95% CI 1.20–2.51) and LN metastasis ( p = .008; pooled OR = 1.72; 95% CI 1.16–2.55) . However, in our study on ICC, TSR was not an independent prognostic factor for survival ( p = .189, HR = 1.399, 95% CI 0.848–2.309 for OS; p = .488, HR = 1.160, 95% CI 0.763–1.763).…”
Section: Discussioncontrasting
confidence: 54%
“…Our results are in concordance with previous studies. A meta‐analysis on 14 studies showed that stroma‐rich tumors show poor overall survival and disease‐free survival of patients with several types of solid tumors, like breast, colorectal, lung, and liver tumors . The patients of these studies were similarly divided into stroma‐rich and stroma‐poor groups according to the best cutoff of 50% because the prognostic difference between the two groups was most significant under this threshold .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the stroma could be fibroblastic when composed of loose connective tissue or more fibrotic when a dense homogeneous collagenous stroma is found, while the size of tumor cell nests which are defined as clusters of tumor cells surrounded by stroma can also be important prognostic parameters. These factors have shown important prognostic significance in various forms of cancer, like colorectal, breast, and lung carcinomas, and from HNSCC, only in oral cancer …”
Section: Introductionmentioning
confidence: 99%
“…The synthesized data suggested that decreased level of serum apoA1 was significantly correlated with some phenotypes of tumor progression, such as larger tumor size, poor histological grade, and advanced clinical stage. All these aggressive tumor behaviors have been documented to be independent factors related to tumor progression and compromise survival outcome [49, 50]. Herein, apoA1 played an important role in the inhibition of tumor progression through different pathways.…”
Section: Discussionmentioning
confidence: 99%